A novel approach for temperature sensing and monitoring through wireless sensor using IoT (International Journal of Engineering and Computer Science, 2016)
Advancement in Science and Technology have always helped us to live more happily. Through research and development, new innovations have made our life more peaceful and happier. Internet of Things (IoT) is one such technology which is developing at a very high pace. The proposed system is to make a system, using IoT, which senses the room temperature and sends this data to a cloud for further analysis and/or action. The proposed system has a wide area of application. Some of which are home automation, fire detection in labs, mines, etc.